2017
DOI: 10.18671/scifor.v45n114.15
|View full text |Cite
|
Sign up to set email alerts
|

Influência das variáveis climáticas na produção florestal via modelo 3-PG no Norte de Minas Gerais

Abstract: Este trabalho teve por objetivo avaliar a influência das variáveis climáticas sobre a produção de plantios de Eucalyptus spp. na região Norte de Minas Gerais utilizando o modelo ecofisiológico de crescimento 3-PG (Physiological Principles in Predicting Growth). O 3-PG foi executado com base em médias históricas e mensais obtidas pelo INMET (Instituto Nacional de Meteorologia) e satélite TRMM (Tropical Rainfall Measuring Mission). A correlação linear (Pearson) (r), coeficiente de determinação (R²), erro padrão … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0
1

Year Published

2019
2019
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
1
1
0
1
Order By: Relevance
“…In the present study, the male gender predominance (79%) and those with age ≤ 50 years (38%) came in concordance with those reported in studies of same interest [10,11] and other studies reported that perianal abscesses are seen two times more frequently in men than in women [2,4,12]. In agreement with our finding, it was stated that the peak incidence of perianal abscesses is in the third or fourth decade of life and it is two or three times more common in men than women with diabetes and increased BMI as the major traced risk factors for development of perianal abscesses [13,14 ].…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, the male gender predominance (79%) and those with age ≤ 50 years (38%) came in concordance with those reported in studies of same interest [10,11] and other studies reported that perianal abscesses are seen two times more frequently in men than in women [2,4,12]. In agreement with our finding, it was stated that the peak incidence of perianal abscesses is in the third or fourth decade of life and it is two or three times more common in men than women with diabetes and increased BMI as the major traced risk factors for development of perianal abscesses [13,14 ].…”
Section: Discussionsupporting
confidence: 92%
“…A análise de séries temporais é a abordagem sistemática pela qual se responde à questão de dados correlacionados no tempo. O estudo de séries temporais tem se mostrado de grande utilidade em várias áreas, como no estudo De Oliveira et al (2017), no qual |Tendência e sazonalidade do regime térmico e de pluviosidade do município de Bandeirantes/PR| O estudo do padrão das variáveis climáticas de uma determinada região é uma preocupação constante dos pesquisadores da área de climatologia e meteorologia (BEZERRA, 2015;CARDIM, 2001;CARDOSO et al, 1998;CURI, 1984;LOMBARDI NETO e BRUGOWICH, 1994;SILVA et al, 2003a;VERONESE e GUIMARÃES, 2002).…”
Section: Introductionunclassified
“…In Brazil, agricultural production has become fundamental for society and the economy, due to its importance in the composition of the gross domestic product (GDP) and because it is determinant for the food security of the population (Oliveira et al, 2018). The 2018/19 harvest showed an estimate of 241.3 million tons of grain, that is, around 6% or 13.7 million tons (t) higher than the previous harvest.…”
mentioning
confidence: 99%